Narrative diaries in the paediatric intensive care unit: A thematic analysis. Issue 1 (13th July 2021) - Sansone, Vincenza; Cancani, Federica; Gagliardi, Chiara; Satta, Tiziana; Cecchetti, Corrado; de Ranieri, Cristiana; Di Nardo, Matteo; Rossi, Angela; Dall'Oglio, Immacolata; Alvaro, Rosaria; Tiozzo, Emanuela; Gawronski, Orsola
Abstract: Background: The paediatric intensive care unit (PICU) diary is a shared tool, kept at the patient bedside, written by relatives and health care providers. There is little evidence about its feasibility and how it supports the families of children admitted to the PICU. Currently, there is no evidence about how the PICU diary is used and what we can learn from it. Aim: To explore the contents of narrative PICU diaries in an Italian PICU. Study design: Qualitative study of PICU diaries conducted with a narrative research approach. Methods: Children sedated and mechanically ventilated for >48 hours were enrolled in a six‐bed Italian PICU of a tertiary care paediatric hospital. During the child's PICU admission, caregivers, relatives, friends, and health care providers were invited to report events, thoughts, and messages, and attach drawings/pictures for the child in the PICU diary. A thematic analysis of the PICU diary contents was performed. Results: Thirteen PICU diaries were completed between August and December 2020, mainly by parents (n = 95; 45%) and health care providers (n = 52; 25%). Three main themes emerged: "Social and spiritual support, " "Caregiver's emotions, feelings and distress, " and "PICU life." Diaries offer insight into caregivers' emotions, social support, clinical activities, and interactions with health care providers, and on progression towards recovery. Conclusion: PICU diaries are valuable in facilitating family‐centred care by providing a space for the written account of the child's admission by parents, other visitors, and health care providers. Relevance to clinical practice: PICU diaries support the relationship and the communication between the family and the team; they provide an informal account of the emotions and needs of parents that has the potential to improve mutual understanding and family‐centred care. Social support and spiritual support are key elements reported by parents for coping with their child's PICU admission.